A strategy for the implementation of standard data structures in financial management information systems - a South African case study - Koekemoer, Silma; Von Solms, Rossouw (African journal of business and economic research, 2021)
Strategy denotes the plans an organisation makes to achieve a set of goals or objectives. An information technology (IT) strategy represents one pillar of a strategy triangle, consisting of a business, organisational and IT strategy, and depends on the perspective, either in support of the business strategy as a master plan for the IT function, or based on the role of IT within the organisation. This paper focused on a strategy for the implementation of standard data structures in financial management information systems. The research employed a pragmatic philosophy resulting in a practical solution to remedy a real problem. It used the design science methodology and principles of case study and action research. The data were collected from 25 municipalities over a three-year period (2014-2016) and culminated in a suitably generic implementation strategy to be used broadly for this and similar IT projects. The research was limited to municipalities in South Africa only, but the resultant strategy should be useable across the borders and into other business sectors.